Upper and lower body power tests predict serve performance in national and international level male tennis players - Eriksrud, O.; Ghelem, A.; Henrikson, F.; Englund, J.; Brodin, N. (Sport Performance & Science Reports, 2018)
Successful outcome of the tennis serve is primarily dependent on speed (1), which is a result of e ective full kinetic chain function (2-5). Speci c mechanical determinants, kinetic and kinematic variables, that contribute to serve speed have been identi ed (2, 4, 6-9). However, current tests of physical tness in tennis do not target all mechanical determinants (10-20). Implementation of tests that target known mechanical determinants in full kinetic chain movements have been called for (3, 21). Aim.Determine the relationship between full kinetic chain tests of dynamic postural control, force and power that target known mechanical determinants of tennis serve performance.